Pengaruh Digitalisasi Perbankan Terhadap Loyalitas Nasabah Dimediasi Kepuasan Nasabah Pada Bank Kalsel Cabang Utama - Dea Silvana Rachmawati; Fitriyadi (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: The objective of this study is to examine and analyze both the direct and indirect effects of banking digitalization on customer loyalty, with customer satisfaction as a mediating variable. This research employs a quantitative approach using the PLS-SEM method, incorporating both outer model and inner model evaluations. Data were collected through the distribution of questionnaires via Google Forms. The population of this study consists of customers of Bank Kalsel at the Main Branch in Banjarmasin, with a total of 150 respondents selected using purposive sampling techniques. The results of this study indicate that banking digitalization and customer satisfaction have a positive and significant effect on customer loyalty. Furthermore, the indirect effect of banking digitalization on customer loyalty, mediated by customer satisfaction, also shows a positive and significant influence